Thermal Environment–Induced Changes in The Physiological Parametersand Growth of Broiler Chickens - Nurhidayah, Asma'ul Fitriana; Ulupi, Niken; Salundik (Faculty of Animal Science, Universitas Brawijaya, 2025)
This study investigated the impact of temperature differences on broiler chickens’ blood profiles and performance. The experiment used two thermal environments, 20°C (T20) and 30°C (T30), which represent comfortable and heat-stress conditions, respectively. An 80-DOC (day-old chick) Ross strain broiler was incubated in two broiler houses. The temperature and relative humidity were measured daily. The temperature and relative humidity were measured daily. Blood samples were collected once at the end of the fifth week, while performance measurements were recorded during the nursery and treatment periods. The data were analysed descriptively. Broiler chickens in the T20 treatment experienced ambient temperatures of 24–26°C with 74–80% relative humidity, whereas those in the T30 treatment experienced temperatures of 30–32°C with 75–78% relative humidity. The hematological values remained within normal physiological ranges: erythrocytes ranged from 3.16–3.41x106/mm3, haematocrit ranged from 25.47–27.02%, haemoglobin ranged from 10.27–10.43 g%, and leukocytes ranged from 8.65–15.40x103/mm3. Broiler chickens reared at high temperatures presented heat stress, as indicated by the ratio of heterophiles to lymphocytes being 0.59. Heat stress resulted in reduced feed consumption, lower body weight gain, decreased final body weight, and an increased feed conversion ratio.